Functional Genomics Insights Into the Pathogenicity, Habitat Fitness, and Mechanisms Modifying Plant Development of Rhodococcus sp. PBTS1 and PBTS2 - Vereecke, Danny; Zhang, Yucheng; Francis, Isolde M.; Lambert, Paul Q.; Venneman, Jolien; Stamler, Rio A.; Kilcrease, James; Randall, Jennifer J. (Frontiers in Microbiology, 2020)
Pistachio Bushy Top Syndrome (PBTS) is a recently emerged disease that has strongly impacted the pistachio industry in California, Arizona, and New Mexico. The disease is caused by two bacteria, designated PBTS1 that is related to Rhodococcus corynebacterioides and PBTS2 that belongs to the species R. fascians. Here, we assessed the pathogenic character of the causative agents and examined their chromosomal sequences to predict the presence of particular functions that might contribute to the observed co-occurrence and their effect on plant hosts. In diverse assays, we confirmed the pathogenicity of the strains on ‘UCB-1’ pistachio rootstock and showed that they can also impact the development of tobacco species, but concurrently inconsistencies in the ability to induce symptoms were revealed. We additionally evidence that fas genes are present only in a subpopulation of pure PBTS1 and PBTS2 cultures after growth on synthetic media, that these genes are easily lost upon cultivation in rich media, and that they are enriched for in an in planta environment. Analysis of the chromosomal sequences indicated that PBTS1 and PBTS2 might have complementary activities that would support niche partitioning. Growth experiments showed that the nutrient utilization pattern of both PBTS bacteria was not identical, thus avoiding co-inhabitant competition. PBTS2 appeared to have the potential to positively affect the habitat fitness of PBTS1 by improving its resistance against increased concentrations of copper and penicillins. Finally, mining the chromosomes of PBTS1 and PBTS2 suggested that the bacteria could produce cytokinins, auxins, and plant growth-stimulating volatiles and that PBTS2 might interfere with ethylene levels, in support of their impact on plant development. Subsequent experimentation supported these in silico predictions. Altogether, our data provide an explanation for the observed pathogenic behavior and unveil part of the strategies used by PBTS1 and PBTS2 to interact with plants.